Association between oral contraceptive use and incident heart failure. (9th April 2021) - Luo, Dongling; Li, Hezhi; Chen, Pengyuan; Xie, Nanshan; Yang, Ziyang; Zhang, Caojin
Abstract: Aims: Oral contraceptives (OCs) are widely used in women of reproductive age, but their influences on heart failure (HF) development have yet to be reported. This study was performed to assess HF risk associated with OC use. Methods and results: We studied women participating in the Multi‐Ethnic Study of Atherosclerosis with available data on OC use. Inverse probability of treatment weighting analyses were used to reduce baseline imbalances. Cox proportional hazards models were applied to evaluate the associations of OC use and HF risk. The primary analysis comprised a total of 3594 participants [average age 62.10 (10.24) years]. During an average follow‐up of 12.45 (3.75) years, 138 incident HF occurred. In unadjusted Cox model, OC use was associated with a decreased risk of HF [hazard ratio (HR) = 0.45, 95% confidence interval (CI) 0.31–0.64, P < 0.001]. However, in multivariable‐adjusted and inverse probability of treatment weighting models, the results were attenuated and became non‐significant (HR = 0.96, 95% CI 0.63–1.48, P = 0.86 and HR = 0.79, 95% CI 0.45–1.40, P = 0.43, respectively). Duration of OC use was not related to increased risks of HF. When stratifying HF into subtypes, similar associations were observed. In multivariable–adjusted regression models, OC use was positively associated with left ventricular end‐diastolic mass [coefficient ( β ) = 3.04, P = 0.006] and stroke volume ( β = 1.76, P = 0.01 for the left ventricle; β = 2.17, P = 0.005 for the right ventricle) but had no impact on left ventricular ejection fraction ( β = 0.09, P = 0.75) and right ventricular ejection fraction ( β = 0.33, P = 0.25). Conclusions: Oral contraceptive use in women of reproductive age does not portend increased risk of HF. However, whether the formulations or dosages differently impact this association should be further investigated.